2018
DOI: 10.1186/s12885-018-5185-9
|View full text |Cite
|
Sign up to set email alerts
|

Dihomo-γ-linolenic acid inhibits xenograft tumor growth in mice bearing shRNA-transfected HCA-7 cells targeting delta-5-desaturase

Abstract: BackgroundWe previously demonstrated that knockdown of delta-5-desaturase via siRNA transfection together with dihomo-γ-linolenic acid supplementation inhibited colon cancer cell growth and migration, by promoting the production of the anti-cancer byproduct 8-hydroxyoctanoic acid from Cyclooxygenase-2-catalyzed dihomo-γ-linolenic acid peroxidation. Here, we extend our study to investigate the effects of delta-5-desaturase-knockdown and the resulting intensified dihomo-γ-linolenic acid peroxidation in xenograft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 47 publications
2
19
0
Order By: Relevance
“…Recent studies from the Qian group revealed that the COX-2-catalyzed peroxidation of dihomo-γ-linolenic acid (DGLA, an upstream ω-6 fatty acid) can produce a distinct anti-cancer byproduct, 8-hydroxyloctanoic acid (8-HOA), which may act as a histone deacetylase inhibitor (HDACi) in an autocrine manner to suppress cancer cell/tumor growth and migration [25], [26], [27], [28], [29], [30], [31], [32], [33], [34]. However, DGLA can be effectively converted to its downstream ω-6 fatty acid arachidonic acid by delta-5-desaturase (D5D), which greatly restricts DGLA's bioavailability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies from the Qian group revealed that the COX-2-catalyzed peroxidation of dihomo-γ-linolenic acid (DGLA, an upstream ω-6 fatty acid) can produce a distinct anti-cancer byproduct, 8-hydroxyloctanoic acid (8-HOA), which may act as a histone deacetylase inhibitor (HDACi) in an autocrine manner to suppress cancer cell/tumor growth and migration [25], [26], [27], [28], [29], [30], [31], [32], [33], [34]. However, DGLA can be effectively converted to its downstream ω-6 fatty acid arachidonic acid by delta-5-desaturase (D5D), which greatly restricts DGLA's bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…However, DGLA can be effectively converted to its downstream ω-6 fatty acid arachidonic acid by delta-5-desaturase (D5D), which greatly restricts DGLA's bioavailability. Thus, a D5D knockdown strategy ( via siRNA transfection) was proposed and demonstrated to successfully limit the conversion from DGLA to arachidonic acid and promote 8-HOA formation, thereby inhibiting cancer cell growth and migration [29], [30], [31], [32], [33], [34]. The promoted 8-HOA was found to induce p53-dependent apoptosis and cause DNA damage as a result of inhibiting histone deacetylase (HDAC) in various types of cancer [29], [30], [31], [32], [33], [34].…”
Section: Introductionmentioning
confidence: 99%
“…DGLA is a substrate of prostaglandin‐endoperoxide synthase 2, giving rise to prostaglandin E1 (PGE 1 ), an inflammation‐suppressing eicosanoids 44,45 . Thus, the anti‐inflammatory property of DGLA and its ability to compete with AA in the synthesis of pro‐inflammatory products may reduce risk of colorectal cancer 45,46 . As for EDA, a previous study found that EDA was inversely associated with colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…injection, 0.5 mL U-100 Insulin Syringe, 29G × 1/2, twice a week, 20 μM in 50 μL PBS), and DGLA+ 3WJ-EpCAM-D5D siRNA nanoparticle group. 49 All of the treatments were for 4 weeks. At the end of the treatment, nude mice were euthanized with an overdose of pentobarbital (200 mg/kg, intraperitoneally [i.p.]).…”
Section: Methodsmentioning
confidence: 99%
“…The tumors were also visualized by the Vevo 3100 VisualSonics Imaging System (FUJIFILM VisualSonics, Toronto, ON, Canada) weekly. 49 …”
Section: Methodsmentioning
confidence: 99%